Elevated INR in a COVID‐19 patient after concomitant administration of favipiravir and warfarin: A case report. (2nd August 2021) - Sekimoto, Masao; Imai, Toru; Hidaka, Shinji; Chiba, Nobutaka; Sakurai, Atsushi; Hata, Mitsumasa; Kikuchi, Norikazu
Abstract: What is known and objective: Favipiravir is a promising treatment candidate for managing coronavirus disease 2019 (COVID‐19). Warfarin has many drug interactions, but no interactions with favipiravir have been reported. Case summary: Our patient was taking warfarin for deep vein thrombosis. The international normalized ratio (INR) was stable (1.65 to 2.0); however, it increased to 4.63 after administering favipiravir. The patient had no other factors justifying this change. What is new and conclusion: Favipiravir and warfarin might have previously unidentified drug interactions that elevated the INR. Therefore, INR must be closely monitored when they are concomitantly administered in COVID‐19 patients. Abstract : It is important to evaluate the drug–drug interactions between the limited antiviral drugs used in COVID‐19 and the drugs used to manage common comorbidities. We report a case of elevated anticoagulant action i.e., international normalized ratio (INR), when favipiravir and warfarin were used concomitantly in a patient with COVID‐19.